The Principles of Legitimacy in Islam and its Influence upon the Muslim - Wafa, Hayatullah (Integrated Journal for Research in Arts and Humanities, 2024)
Some beliefs that the Islamic government in an unpopular and undemocratic government where the rights of the ruler is the bulk of the people-including the rights for determination type of government and the rulers-are ignored so the religious government lacks rational legitimacy, is the election and admissibility of the people. Hence, some have called for the addition of a "democratic" clause to the "religious rule" theory. In this study, contrary of this idea, show that Islam fourteen centuries ago paid special attention to popular legitimacy and based its government on acceptance and election in this study, we discuss that Islam forms a government and determines its type and ruler. It enumerates the rights of Muslims and the community, but because of Prophet Mohammad.